CODE SWITCHING USED BY ENGLISH TEACHER AT ISLAM TIRTAYASA JUNIOR HIGH SCHOOL (EIGHT GRADE) - Lia Amalia; Riki Gunawan (Journal of English Language Teaching and Literature (JELTL), 2021)
Objective of this research is to explain the use of code switching by English teachers in classroom during learning activities. This research uses qualitative approach with a case study design, the research subject is an English teacher at Islam Tirtayasa Junior High School. Collecting data in this study using data display, data reduction and drawing conclusions. The focus of this research is the use of code switching by English teachers in online classroom during the learning process and the sub focus of the research is the types of code switching used by the English teacher and the reasons for using code switching. The result of this research is to find the type of code switching usage and the reasons for using code switching by English teachers in online classroom during the learning process. The conclusion is there are three types of code switching used by English teachers during the learning process in the classroom. Namely: First, inter sentential code switching, which is 64 times. Second, Intra-sentential code switching 31 times. Third, Tag switching 10 times. Then some reasons why English teachers use code switching, namely: First, Talking about Particular topic. Second is Interjection. Third is Repitition for Clarification. Fourth is Expressing for Group Identity